The potential of berula erecta in vitro for As bioaccumulation and phytoremediation of water environments. Issue 1 (31st December 2023) - Ambrožič-Dolinšek, Jana; Podgrajšek, Anja; Šabeder, Nik; Grudnik, Zdenka Mazej; Urbanek Krajnc, Andreja; Todorović, Biljana; Ciringer, Terezija
ABSTRACT: A potential plant species suitable for As bioaccumulation and phytoremediation of water environments could be the macrophyte Berula erecta. The objective of the present study was to investigate the effect of arsenate (As(V), C2H6AsNaO2∙3 H2O), predominant in freshwater systems, on the growth, development and low molecular weight thiols of Berula erecta under controlled tissue culture conditions in vitro . Uptake of total arsenate increased with increasing arsenate treatments, at a higher percentage in the roots than in the aboveground parts of the plants. Lower concentrations of As(V) (0.1, 1, 10 mg L−1) had a positive effect on growth, dry weight, length of roots and shoots and number of buds. High concentrations of arsenate (50 and 100 mg As(V) L−1) significantly inhibited all growth parameters and decreased the photochemical efficiency of PSII. Evaluation of thiols revealed the critical As level (146 µg g−1 DW; 50 mg As(V) L−1 treatment) above which the As concentration can be toxic.